ON BREEDING AND REARING THE FRESHWATER PRAWN MACROBRACHIUM CHOPRAI IN CLOSED WATER SYSTEMS - Prakash, Shree; Wishard, S K; Saxena, R K (Indian Journal of Fisheries, 2011)
Experiments were conducted in laboratory and yard on breeding and larval-rearing of the north Indian freshwater prawn, Macrobrachium choprai, using20-1 glass jars with or without water recirculatory arrangement, 25-1 inverted belljar with water recirculation and refilling arrangement and plastic pools of threefootdiameter having either floating cotton cage or air pump with filter bed andrecirculatory filtering system. The main feed consisted of egg powder, fish powder,green water, green water plus Probofex, green water plus Orabolin and mixtureof RP, GOC and dried plankton. Green water plus Orabolin accelerated thegrowth, producing postlarva in 19 days in floating hatchery exhibting all- adultcharacters. The same stage of growth was obtained in 30 days in green waterplus Probofex.